Implementation of Three Good Things in Life Training on Subjective Wellbeing Improvement in Student Master Degree of Professional Psychology - Setiawan, Mohammad Fauzi; Yoenanto, Nono Hery (Universitas Muhammadiyah Metro, 2019)
This study aims to determine whether the application of the three things good gymnastics in life effectively improves the subjective welfare of psychology professional students. The three good things exercise Martin Saligman introduced that as a method of psychological intervention; More specifically, this method is one of the intervention methods with a positive psychological approach. The subjects of this study were 13 students of the professional psychology master program at Airlangga University, Surabaya. The data collection used a survey method, with a subjective welfare measure, namely the PERMA questionnaire introduced by Seligman in 2005 and translated into Indonesian. The data analysis technique used non-parametric statistical analysis with the Wilcoxon Signed Rank Test different test techniques with SPSS 16 for Windows software. The results showed a significance value of p of 0.003, which indicates a value of <0.05, conclude that three good things in life exercise effectively improve the personal welfare of professional psychology students. The results of the descriptive analysis of the PERMA score include elements of positive emotions, attachment, relationship, meaning, and achievement, which indicate an increase between before receiving treatment (pre-test) and after receiving treatment (post-test).